Invasive Pneumococcal Disease: Still Lots to Learn and a Need for Standardized Data Collection Instruments - T. J. Marrie; G. J. Tyrrell; Sumit R. Majumdar; Dean T. Eurich (Canadian Respiratory Journal)
Background. Large studies of invasive pneumococcal disease (IPD) are frequently lacking detailed clinical information. Methods. A population-based 15-year study of IPD in Northern Alberta. Results. 2435 patients with a mean age of 54.2 years formed the study group. Males outnumbered females and Aboriginal and homeless persons were overrepresented. High rates of smoking, excessive alcohol use, and illicit drug use were seen. Almost all (87%) had a major comorbidity and 15% had functional limitations prior to admission. Bacteremia, pneumonia, and meningitis were the most common major manifestations of IPD. Almost half of the patients had alteration of mental status at the time of admission and 22% required mechanical ventilation. Myocardial infarction, pulmonary embolism, and new onset stroke occurred in 1.7, 1.3, and 1.1% of the patients, respectively; of those who had echocardiograms, 35% had impaired ventricular function. The overall in-hospital mortality was 15.6%. Conclusions. IPD remains a serious infection in adults. In addition to immunization, preventative measures need to consider the sociodemographic features more carefully. A standard set of data need to be collected so that comparisons can be made from study to study. Future investigations should target cardiac function and pulmonary embolism prevention in this population.